Integration of EST-SSR markers of Medicago truncatula into intraspecific linkage map of lentil and identification of QTL conferring resistance to ascochyta blight at seedling and pod stages - Gupta, D.; Taylor, P.; Inder, P.; Phan, H.; Ellwood, Simon; Mathur, P.; Sarker, A.; Ford, R. (Springer, 2011)
Microsatellite markers have been extensively utilised in the leguminosae for genome mapping and identifying major loci governing traits of interest for eventual marker-assisted selection (MAS). The lack of available lentil-specific microsatellite sequences and gene-based markers instigated the mining and transfer of expressed sequence tag simple sequence repeat (EST-SSR)/SSR sequences from the model genome Medicago truncatula, to enrich an existing intraspecific lentil genetic map. A total of 196 markers, including new 15 M. truncatula EST-SSR/SSR, were mapped using a population of 94 F5 recombinant inbred lines produced from a cross between cv. Northfield (ILL5588) × cv. Digger (ILL5722) and clustered into 11 linkage groups (LG) covering 1156.4 cM. Subsequently, the size and effects of quantitative trait loci (QTL) conditioning Ascochyta lentis resistance at seedling and pod/maturity stages were characterised and compared. Three QTL were detected for seedling resistance on LG1 and LG9 and a further three were detected for pod/maturity resistance on LG1, LG4 and LG5. Together, these accounted for 34 and 61% of the total estimated phenotypic variation, respectively, and demonstrated that resistance at the different growth stages is potentially conditioned by different genomic regions. The flanking markers identified may be useful for MAS and for the future pyramiding of potentially different resistance genes into elite backgrounds that are resistant throughout the cropping season.